THEORY OF INTEGRAL INDIVIDUALITY BY V. S. MERLIN: HISTORY AND NOWADAYS - B. A. Vyatkin; L. Ya. Dorfman (Russian State Vocational Pedagogical University, 2017)
The study is devoted to overview and analysis of V. S. Merlin' theory of integral individuality.The aim of the study is to reveal a system's background of the theory of integral individuality; to designate its current issues and to put new tasks of its further advancement.Methodology and research methods. Problematic and comparative analyses are used. A systematization of the main assumptions of the theory by V. S. Merlin shows that it is based on a general systemic approach and current ideas about integration.Results. It is demonstrated that the system-based approach provides a multi-focus perspective to view the integral individuality. Mostly, the following system ideas are embedded in V. S. Merlin's theory. They are the concepts of structural levels, teleology, and polymorphism. With respect to the theory of integral individuality, a human is shown as a big system. It consists of a hierarchical set not included in each other, but relatively autonomous operative multilevel subsystems. They link one to another in a polymorphic multi-valued (many-tomany) way. The main features of integral individuality are seen as the hierarchical arrangement and levels, integration and differentiation, teleology and causality, flexibility of polymorphic links (between levels) and rigidity of causal links (within levels). In spite of its maturity, this theory can be put in a further progress. This perspective has been elaborated based on three key ideas - multi-quality, commonality, and isomerism.Scientific novelty. The routes of the phenomenon of integral individuality are uncovered. Its main properties are described: a systemic version of integrity, hierarchy, and polymorphism. Some topical problems are highlighted within the theory of integral individuality. Next tasks can be set to further develop the theory of integral individuality. They focus on shift from the systemic viewpoint to a multi-systemic outline, to combine integrity and commonality, to provide an isomerism coming from the polymorphic framework.Practical significance. The materials and thesis stressed in this article can be useful for researchers studying holistic conceptions of human. The theory of integral individuality can guide investigations designated to test Merlin's assumptions under various conditions.